The Application of Video Assisted Discovery Learning Models to Improve Critical Thinking Skills - Mutia Shafira; Luki Yunita; Miessya Wardani (Journal of Educational Chemistry (JEC), 2026)
Students' critical thinking skills in science education, especially chemistry, are still relatively low due to a learning process that tends to be teacher-centered and the use of learning media that has not been optimally utilized. One effort to improve critical thinking is through the application of a video-assisted discovery learning model. This study aims to describe the improvement in students' critical thinking skills through the application of a video-assisted discovery learning model on buffer solution material. This study uses a descriptive approach with quantitative methods. The research sample consisted of 30 students in class XII Sainkes 1 SMAN 1 Parung in the 2024/2025 academic year, selected using purposive sampling techniques. The instrument used was an essay test based on five aspects of critical thinking according to Ennis. Data analysis techniques were carried out descriptively and quantitatively with the help of Microsoft Excel to process and present the data in the form of percentages. The results showed that students' critical thinking skills improved in the posttest, with percentages of 64.39% in providing simple explanations, 65.92% in building basic skills, 69.46% in drawing conclusions, 75.69% in providing further explanations, and 68.33% in organizing strategies and tactics. These findings indicate that the application of the video-assisted discovery learning model can improve students' critical thinking skills in buffer solution material.